Cooling and freezing effects on development of flies of forensic importance - Carriço, Cesar; Caetano, Rebecca Leal; Barbosa, Júlio Vianna; Pinto, Zeneida Teixeira (EntomoBrasilis, 2019)
Abstract. Cooling and freezing experiments were carried out at Oswaldo Cruz Foundation (Fiocruz / RJ). Flies colonies were established from specimens collected at the campus using a baited trap, as described for the species: Chrysomya putoria (Wiedemann), Chrysomya megacephala (Fabricius), Lucilia cuprina (Wiedemann), Musca domestica Linnaeus, Peckia ruficornis (Fabricius) and Peckia chrysostoma (Wiedemann). Prolonged exposures at lethal low temperatures can produce deleterious effects (including death) even if the insect does not freeze; during long-term exposure to low temperatures, the organisms may finally die from the exhaustion of energy reserves. Efeitos do resfriamento e congelamento no desenvolvimento de moscas de importância forense Resumo. Experimentos de resfriamento e congelamento foram realizados na Fundação Oswaldo Cruz (Fiocruz / RJ). Colônias de moscas foram estabelecidas a partir de espécimes coletados no campus usando uma armadilha com isca, conforme descrito para as espécies: Chrysomya putoria (Wiedemann), Chrysomya megacephala (Fabricius), Lucilia cuprina (Wiedemann), Musca domestica Linnaeus, Peckia ruficornis (Fabricius) e Peckia chrysostoma (Wiedemann). Exposições prolongadas em baixas temperaturas podem produzir efeitos deletérios (incluindo morte) mesmo se o inseto não congelar; durante a exposição prolongada a baixas temperaturas, os organismos podem morrer pelo esgotamento das reservas de energia.